2019
DOI: 10.1002/jmri.26717
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility of 3D MR fingerprinting relaxometry measurements in normal breast tissue

Abstract: Background The 3D breast magnetic resonance fingerprinting (MRF) technique enables T1 and T2 mapping in breast tissues. Combined repeatability and reproducibility studies on breast T1 and T2 relaxometry are lacking. Purpose To assess test–retest and two‐visit repeatability and interscanner reproducibility of the 3D breast MRF technique in a single‐institution setting. Study Type Prospective. Subjects Eighteen women (median age 29 years, range, 22–33 years) underwent Visit 1 scans on scanner 1. Ten of these wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…More recently, 3D MRF with Bloch–Siegert B 1 + map correction and fat suppression was used to acquire full‐volume, T 1 and T 2 maps in the breast at a spatial resolution of 1.6 × 1.6 × 3 mm 3 in ~6 minutes . Panda et al conducted both repeatability and reproducibility studies in healthy subjects . In the work by Chen et al, MRF maps were useful in characterizing the breast lesions: T 1 and T 2 relaxation times measured in healthy subjects agreed with previous literature, and the T 2 relaxation time was significantly higher in invasive ductal carcinoma than in healthy tissue …”
Section: Potential Clinical Usesmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, 3D MRF with Bloch–Siegert B 1 + map correction and fat suppression was used to acquire full‐volume, T 1 and T 2 maps in the breast at a spatial resolution of 1.6 × 1.6 × 3 mm 3 in ~6 minutes . Panda et al conducted both repeatability and reproducibility studies in healthy subjects . In the work by Chen et al, MRF maps were useful in characterizing the breast lesions: T 1 and T 2 relaxation times measured in healthy subjects agreed with previous literature, and the T 2 relaxation time was significantly higher in invasive ductal carcinoma than in healthy tissue …”
Section: Potential Clinical Usesmentioning
confidence: 99%
“…In a phantom, when ground truth values are available, the bias of that method from the ground truth values should be presented, as shown in Fig. using data from Ma et al Ideally, the phantom is used not for a single validation, but repeatedly removed and then positioned in the scanner and imaged to generate repeatability data, as done in one day by Anderson et al, over multiple days on one system by Jiang et al, and reproducibility data, as done across three MRI systems by Cloos et al Repeatability and reproducibility data are also needed in vivo, and some studies were recently completed . Cloos et al presented results from a small study using three healthy controls, with two measurements across three systems.…”
Section: Barriers To Clinical Adaptation and Recommendations For Progmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate in vivo MRF studies on hip cartilage, 55 brain, 62,63 cardiac tissue 64 and breast 65 showed good repeatability and reproducibility across scanners. In particular, repeatability coefficients of variation for T 1 and T 2 in the brain study were below 8% and 14%, respectively, 62 while it was better in breast tissue, ranging from 3 to 4% for T 1 and 5 to 7% for T 2 .…”
mentioning
confidence: 91%
“…. Additionally, sequences have been modified for areas beyond neuro, including applications in the abdomen, breast, prostate, cardiac, knee and hip, among others. Examples from several of these works are presented in Fig.…”
mentioning
confidence: 99%